Treating Concomitant Advanced Heart Failure and Advanced Cancer With Left Ventricular Assist Device, Surgery, and Biologics - Blake Campbell, MD; Arianne Clare Agdamag, MD; Halle C.F. Moore, MD; Paulino Alvarez, MD, MPH (JACC: Case Reports, 2025)
The diagnosis of cancer in the context of evaluation for advanced heart failure therapies represents a psychosocial and therapeutic challenge. We present a case report of a patient with breast cancer diagnosed during heart transplantation evaluation. A 63-year-old female presented with anterior ST-segment elevation myocardial infarction and severe left ventricular dysfunction 2 months prior. She was readmitted because of heart failure decompensation and diagnosed with inotrope-dependent stage D heart failure. Routine pre–heart transplantation evaluation diagnosed Stage IIIb breast cancer. She underwent left ventricular assist device (LVAD) implantation, neoadjuvant chemo-immunotherapy, mastectomy, adjuvant radiation, and adjuvant immunotherapy. Three years after LVAD implantation, she is at home with cancer in remission. There are no direct guidelines for the management of active cancer in the setting of advanced heart failure. Multidisciplinary teams should rapidly evaluate patients with cancer and advanced heart failure to plan life-saving cardiac and oncologic therapies. The treatment of cancer in LVAD patients is an important area for future expansion of guidelines.